Americans and Return Migrants in the 1881 Scottish Census - Tahitia L. McCabe (Genealogy)
This article reveals basic demographic information on Americans and Scottish return migrant parents of the 1321 American children listed in the 1881 Scottish census and investigates reasons for return migration from America to Scotland. Census information was downloaded into an Excel spreadsheet and data including occupation, age, relation to head of household, place of residence and length of time back in Scotland, were counted and listed. General causes of return migration are explored and specific reasons for migrants, especially coal miners, to return to Scotland are briefly touched upon; covering the economic downturn in America during the mid-1870s and tensions towards immigrants in the United States during this period. The results of a deeper genealogical study of four families are reported. More than two-thirds of the parents of American children listed were Scottish with others primarily Irish and English. There was a wide range of occupations with construction and coal mining having the greatest numbers. Most families were living in Lanarkshire and Midlothian but 28 other Scottish counties were found as places of residence. Further research is needed to identify whether American children and their Scottish families are represented in other census years.